Feels so good - Xscape; Sony Music Entertainment (New York : Sony Music Entertainment, 1995)
Contains the full single Feels So Good and five samples from the album Off The Hook.
CD 1 : Feels So Good / (3:32) -- What Can I Do / (1:05) -- Do You Want To / (1:17) -- Hard To Say Goodbye / (1:27) -- Who Can I Run To / (1:30) -- Feels So Good / (1:10).
Koleksi Khas Wiramanja.
Title from disc label.
Keywords: Songs, English